Lama Penggunaan Alat Kontrasepsi Hormonal dengan Kejadian Hipertensi di Puskesmas Sangurara Kota Palu - Hadriani Hadriani; Rafika Rafika (Politeknik Kesehatan Kemenkes Mamuju, 2018)
Hormonal disturbances in the use of estrogen and progesterone synthesis hormone will occur imbalance hormone estrogen and progesterone in the body that will trigger the occurrence of disorders of the blood vessels and vascular conditions that are manifested by the increase in blood pressure. The purpose of this study is to know the relationship between the use of hormonal contraception with hypertension. This type of research is an observational analytic research using cross sectional approach. The research has been carried out in the Working Area of ​​Puskesmas Sangurara Palu City from June to September 2017. The population in this study are all family planning acceptors of Hormonal Family Health Center in Puskesmas Sangurara Kota Palu with population 26,608 people from January until August 2017 with sample size 99 people . Sampling of this research data using slovin formula. The sampling technique used Purposive Sampling technique. Univariate and bivariate data analysis using Chi Square with α 0,05. Based on statistical test, there was no relation between hormonal contraceptive use and hypertension incidence. The conclusion is that there is no relation between the use of hormonal contraceptive devices and the incidence of hypertension, so it is recommended that every hormonal contraceptive acceptor should be monitored for routine side effects Keywords: Hormonal contraception, hypertension occurrence